Efficient digestion and improvement of dewaterability of municipal wastewater treatment sludge through catalytic calcium peroxide/ozonation advanced oxidation process - Abdolmotaleb Seid-Mohammadi; Ghorban Asgari; Reza Shokoohi; Alireza Rahmani; Fatemeh Sahraei; Amir Shabanloo (Cleaner Engineering and Technology)
In the biological treatment process of sanitary wastewater, a large amount of sludge is produced, which has a high spoilage and microbial load, so its treatment and stabilization processes must be considered. The present study aimed to chemically stabilize sludge from the Hamadan wastewater treatment plant using the advanced oxidation process of catalytic calcium peroxide/ozonation (CaO2/O3). The effect of important operational variables such as wastewater pH, CaO2 catalyst dosage, ozone dosage, and reaction time on volatile solids (VS) and volatile suspended solid (VSS) removal was studied. Also, the reduction of sludge volume index (SVI), sludge water content, and specific resistance to filtration (SRF), as well as the reduction of coliforms, were studied. The best operating conditions were obtained at pH = 9, a catalyst CaO2 dose of 1 g/L, an ozone dosage of 2 g/h, and a reaction time of 60 min. The removal of VS and VSS under these conditions was above 90 % and 80 %, respectively. Also, the SVI of the sludge reached less than 80 mL/g, which suggests a good gravity-settling condition. Kinetic analysis revealed that the interaction of O3 and CaO2 in the integrated CaO2/O3 improves sludge COD removal efficiency by around 52.11 % due to their synergistic effect. The water content of the sludge after the reaction decreased from 85.67 % to 46.54 %. On the other hand, the SRF also decreased by about 40 % under the optimized conditions. The synergistic effect of ozone, hydroxyl radicals, and other reactive oxygen species (ROSs) on sludge particles was observed with field emission scanning electron microscopy (FESEM) images, which was clearly evident as destructive effects on sludge particles. According to the results of this research, a catalytic ozonation system with CaO2 can be used as a suitable process to manage the treatment of sludge in the Hamadan wastewater treatment plant.